Comprehensive health care for children and adolescents with congenital disorders: The impact of the COVID-19 pandemic on care - Russoni, Caio; Pereira , Ana Maria Daun Cação; Delambert , Cristina Helena de Lima; Sauretti , Priscila Nalin; Fonseca , Cátia Regina Branco da (Seven Editora, 2023)
Congenital anomalies are structural or functional changes that occur during intrauterine life. Approximately one in five deaths in the neonatal period are due to birth defects in Latin America and the Caribbean. There are several factors for their development, from infections, maternal nutritional status, use of medication, and environmental or genetic factors. Most anomalies are present in low-income countries where we have an inadequate prenatal context, a greater predisposition to infections due to precarious health, and the use of prohibitive substances (medicines and drugs) during pregnancy. From this, we have that several social determinants of health such as social, economic, cultural, ethnic, psychological, and behavioral factors influence the course of a disease in a certain population. When there is a system that integrates health care for children and adolescents with congenital disorders, including genetic syndromes, especially Down syndrome, care for children promotes better growth and development. A comprehensive health care service for children and adolescents inserted in a university hospital must be able to coordinate care actions. During the years 2020 to 2022, health services faced the covid-19 pandemic that the entire population experienced. There was an impact with a reduction in the number of daily visits to these patients and a reduction in the inclusion of new ones, leading to fragmentation or discontinuity of care. DOI:https://doi.org/10.56238/emerrelcovid19-015